Concrete girders retrofitted with basalt fibre fabric – A feasibility study using lab tests and field application. (1st July 2021) - Hughes, Eric; Das, Sreekanta; Van Engelen, Niel; Lawn, David
Highlights: Presents a field study and a detailed lab-based study on RC girders rehabilitation. Compares load-deflection and ductility of rehabilitated specimens with control specimens. Ultimate strength of rehabilitated beams can be restored to that of control specimens. Optimum number of basalt fabric layers is recommended using performance factor. The study found that ACI 440.2R can be used for rehabilitation using basalt fabric. Abstract: Basalt fibre fabric is made of igneous rock called basalt and hence, it is a sustainable material which can be used for strengthening and rehabilitation of structural components. As a part of a long-term research program on applications of basalt fibre and fabric for rehabilitation and strengthening of various structures, in 2016, damaged concrete girders of a road bridge were successfully retrofitted using basalt fibre fabric. There was no lost service time for this structure during and now post repair. The continued performance observed from quarterly bridge inspections clearly demonstrates that this rehabilitation technique is a viable and durable method to retrofit and repair of infrastructure since no signs of distress, damage, or delamination have been noticed. Lab testing on thirteen reinforced concrete beams was also undertaken to determine this retrofitting technique, specifically by testing the performance of concrete beams loaded well beyond the service load. The lab test data confirms the validity of the rehabilitation methodology with outcomes beyond the service and yield loads. The lab test data showed that the yield and ultimate moment capacities of the beams were increased significantly. The retrofitted beams also exhibited a better ductility and performance when compared to the control beam.